Primary undifferentiated pleomorphic cardiac sarcoma with MDM2 amplification presenting as acute left-sided heart failure. (30th September 2018) - Watson, Richard; Frye, Joseph; Trieu, Megan; Yang, Michael X
Abstract : Primary cardiac tumours are a rare clinical entity that can present with myriad of non-specific cardiopulmonary symptoms. We describe a case of a 61-year-old previously healthy woman who presented with progressive dyspnoea and lower extremity swelling, suggestive of acute left-sided heart failure. Transthoracic echocardiogram revealed a large, 3.7×3.2 cm intracardiac mass resulting in severe mitral valvular dysfunction. The patient underwent surgical resection of the mass, however, negative margins were not obtained, and the tumour quickly returned. Histological and molecular analysis was consistent with the diagnosis of undifferentiated pleomorphic sarcoma with murine double minute 2 ( MDM2 ) amplification. Given the overall grim prognosis, the patient chose to pursue comfort-based care. She died at home 9 months after the initial diagnosis. Here, we provide an updated review of the literature for the classification of undifferentiated pleomorphic cardiac sarcoma and potential treatment modalities.